DEVELOPING STUDENT’S ASSESSMENT OF WRITING RECOUNT TEXT BASED ON PROJECT ASSESSMENT FOR TENTH GRADE AT SMK NEGERI 2 BINJAI - Haswani, Fahri Haswani (Journal of Language, Literature and Teaching, 2020)
ABSTRACT The objective of the study is to develop project assessment for student’s writing assessment of recount text and to design the appropriate assessment for Computer Network Enginering students grade X at SMK Negeri 2 Binjai. The study used research and development method.The data of the study were taken from English teacher of Computer Network Engineering grade X at SMK Negeri 2 Binjai. Then the data were analyzed and developed into writing assessment.The average of the project assessment is 4,6 and the percentage is 92% .The result showed that the development of project assessment at SMK Negeri 2 Binjai is categorized “Very Good”. The English writing assessment was developed through six phases, they were; 1. gathering information and data, 2. analyzing data, 3. designing new writing assessments, 4. validating by experts, 5. revising writing assessments, and 6. final product.Keywords: Project assessment, development, writing, Computer Network Engineering. ABSTRAKTujuan dari penelitian ini adalah untuk mengembangkan penilaian proyek penilaian menulis teks recount siswa dan untuk merancang penilaian yang sesuai untuk siswa Teknik Jaringan Komputer siswa kelas X di SMK Negeri 2 Binjai. Kajian ini menggunakan metode penelitian dan pengembangan. Data penelitian ini diambil dari guru Bahasa Inggris Teknik Jaringan Komputer kelas X di SMK Negeri 2 Binjai kemudian dikembangkan menjadi rubrik penilaian projek menulis teks recout. Rata-rata penilaian proyek adalah 4,6 dengannpersentase 92%. Hasil penelitian menunjukkan bahwa pengembangan penilaian proyek di SMK Negeri 2 Binjai dikategorikan “Sangat Baik”. Penilaian penulisan bahasa Inggris dikembangkan melalui enam fase, yaitu; 1. mengumpulkan informasi dan data, 2. menganalisis data, 3. merancang penilaian penulisan baru, 4. memvalidasi oleh para ahli, 5. merevisi penilaian penulisan, dan 6. produk akhir. Kata Kunci: Project assessment, development, writing, Computer Network Engineering.